Spiritual intelligence during catastrophe: the Covid-19 pandemic case - Ab Razak, Ratna Roshida; Mohd Yusoff, Ahmad Nasir; Mohd Isa, Nur Ayuni (Human Resource Management Academic Research Society, 2021)
This study is an attempt to explain the significance role of spiritual intelligence during the complexities and uncertainties, particularly due to the tragedy of the COVID-19 pandemic. Spiritual intelligence is the capacity to behave with insight and humility while preserving inner and outer harmony irrespective of the circumstances. Not only does one with a high spiritual intellect respond appropriately in a particular circumstance or state, but it also analyzes how he or she is in that position. This study also aims to understand how the COVID-10 pandemic could lead someone to adjust, embrace and change life and turn the tragedy into a time of resilience, strength, knowledge and a new environment of mutual and communal living, sharing responsibilities and appreciating solidarity.